Electron microscopy : - Bozzola, John J. (Jones and Barnett, 1991)
This book is the standard work for biological electron microscopists wishing to learn how to prepare their specimens for electron microscopic investigation. This fully revised and expanded fourth edition includes three new chapters covering such topics as plant tissues, immunocytochemistry, and applications of microwave irradiation to microscopy. It provides practical instructions on how to process biological specimens, as well as a detailed discussion on the principles underlying the various processes. Dr. Hayat presents methods in a self-explanatory form and includes alternative procedures and points of disagreement to help the reader interpret data accurately. What sets this book apart from its competition is that it not only describes techniques but also explains their fundamental principles; that is, those chemical reactions underlying the use of various reagents for preserving and staining cellular components.